Muslim community of the Indo-Pakistan subcontinent (610-1947) - Qureshi, Ishtiaq Husain (Delhi, 1985)
The history of the Muslim community of the Indo-Pakistan subcontinent has seldom found its rightful place in historical literature. This is not due to any dearth of material, because the Muslims have been keen recor ders of events. Nor does this history lack elements of interest; even as a tale of adventure it is worth telling. The Muslims established and sustained an empire in the subcontinent which lasted for several centur ies. When it declined and fell, it left in its wake problems which have yet to find a final solution, one of which persists in the unpre dictable relations between India and Pakistan. What little has been written about the Muslims of the subcontinent, deals mostly with the monarchs and their policies. Attracted by their magnificence or impelled by the desire to condemn them, historians have mostly devoted their entire attention to the rulers and none to the people. Thus, there exists an unwarranted ignorance of the psych ologp of the Indo-Pakistan Muslim commu nity, of the thinking of its leaders and masses, and of the history of its origins, developments and integration. For this it has been necessary to go back to the very beginning and to take into consideration the relevant factors in the entire history of the community. The author exposes, in this tudy on the subject, its peculiar situation which has moulded its ideas, its destiny, and integrite
Keywords: Muslims